Unlocking the healing spectrum: a narrative review fusing insights from internal medicine, dermatology, and plastic surgery - Bravo Jiménez, Humberto; Quinapanta Castro, Néstor Israel; Casco Luzuriaga, Lizbeth Denisse; Gordón Villagrán, Ximena Gabriela; Montenegro Salas, Daniela Stephanie; Montiel Fleire, Sainly del Carmen; Mendoza López, María de Jesús; Cushpa Quinapanta, Erik Manuel; Bravo Montes, Angelitte Arlette (Salud Ciencia y Tecnología, 2023)
Introduction: wound healing and tissue regeneration are complex processes influenced by systemic health, local wound environment, and surgical interventions. Despite advances in medical science, non-healing wounds and scarring remain significant clinical challenges. Objective: The objective of this review is to synthesize the contributions of internal medicine, dermatology, and plastic surgery to wound healing and tissue regeneration, highlighting the importance of interdisciplinary approaches in optimizing wound care strategies and patient outcomes.Methods: a comprehensive literature search was conducted in PubMed, Web of Science, and Scopus databases to identify relevant articles on wound healing and tissue regeneration, focusing on the contributions of internal medicine, dermatology, and plastic surgery. The review synthesizes evidence from these studies, emphasizing the importance of systemic health, skin physiology, and surgical interventions in optimizing wound healing and tissue regeneration.Results: this review highlights the complementary roles of internal medicine, dermatology, and plastic surgery in addressing systemic health, skin physiology, and surgical interventions for wound healing and tissue regeneration. Internal medicine addresses systemic health factors that impact wound repair, dermatology focuses on skin physiology and pathology, and plastic surgery provides techniques for functional and aesthetic restoration of tissues. The review emphasizes the importance of interdisciplinary collaboration, patient-centered care, health disparities, and technological advancements in optimizing the healing spectrum.Conclusions: unlocking the healing spectrum requires a comprehensive and interdisciplinary approach that integrates insights from internal medicine, dermatology, and plastic surgery. Addressing systemic health, skin physiology, and surgical interventions is crucial for wound healing and tissue regeneration